2020
DOI: 10.1177/0309364620912642
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review in prosthetics and orthotics education research

Abstract: Background: Formal prosthetic/orthotic education has evolved greatly since its inception in the 1950s. The International Society for Prosthetics and Orthotics has established guidelines and recognition for prosthetic/orthotic programs worldwide. However, the current state-of-the-science in prosthetic/orthotic education is largely unknown. Objectives: To evaluate and synthesize available prosthetic/orthotic education research. Study design: Systematic review. Methods: Three bibliographic databases were searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Vendors can consider subsidizing the equipment used for training and, in return, encouraging wider DT adoption among new practitioners by instilling greater proficiency and confidence with adequate training. 30,33,35…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vendors can consider subsidizing the equipment used for training and, in return, encouraging wider DT adoption among new practitioners by instilling greater proficiency and confidence with adequate training. 30,33,35…”
Section: Discussionmentioning
confidence: 99%
“…Vendors can consider subsidizing the equipment used for training and, in return, encouraging wider DT adoption among new practitioners by instilling greater proficiency and confidence with adequate training. 30,33,35 This study has several limitations. All participants volunteered their involvement with the study; it should be acknowledged that those O&P practitioners might have a more favorable attitude toward DT.…”
Section: Theme 3: Industry Mindset Shift In Embracing Dt Practicementioning
confidence: 96%
“…The identified topics of research included (1) teaching/learning methods such as web-based and e-learning approaches, study abroad experiences, critical thinking development, and education strategies; (2) aspects of curriculum like interprofessional education and general curriculum development; (3) program-level topics such as competency standards, theoretical concepts, and graduate competency; and (4) country/region-level topics such as a description of current clinical practice and education and country-level outcomes. 32 The authors of that review reported a need for high-quality evidence to improve P&O education and to promote global advancement of the P&O profession. P&O educators at academic institutions and clinical/technical sites of the future will have more opportunities to take part in research at any stage.…”
Section: Participate In the Development Of Research Questions Implemmentioning
confidence: 99%
“…The International Society for Prosthetics and Orthotics (ISPO) has established educational standards for P&O occupations and global recognition for P&O programs. 1 In Thailand, formal education in professional education in P&O occupations began about 2 decades ago. In 2019, this program was accredited by the ISPO for creation of prosthetists and orthotists.…”
Section: Introductionmentioning
confidence: 99%